Carbon nitride nanosheet/metal–organic framework nanocomposites with synergistic photocatalytic activities. Issue 13 (17th March 2016) - Hong, Jindui; Chen, Chunping; Bedoya, Franky E.; Kelsall, Geoff H.; O'Hare, Dermot; Petit, Camille
Abstract : Carbon nitride nanosheet/metal–ogranic framework nanocomposites with heterojunction were synthesised via an in-situ method, leading to better electron–hole transfer and more efficient photocatalytic activities. Abstract : Heterogeneous photocatalysis plays a key role in the implementation of novel sustainable technologies, e.g. CO2 conversion into fuel, H2 production from water or organics degradation. The progress of photocatalysis relies on the development of tuneable photocatalysts and particularly the ability to build nanocomposites exhibiting synergistic properties with reduced electron–hole recombination rates. We report for the first time the in situ synthesis of nanocomposites of carbon nitride nanosheets (CNNSs) and metal–organic frameworks (MOFs) for application as photocatalysts. This approach leads to the 'nano-scale mixing' of the components, thereby enabling a greater performance compared to other types of 2D materials/MOF composites typically obtained via physical mixing. The objective is to take advantage of the complementary features of the materials while forming a heterojunction. The structural, chemical, photophysical and electrochemical properties of the nanocomposites are characterized and compared to those of the parent materials and their physical mixture. The nanocomposites retain the high specific surface area and strong visible light absorbance of MIL-100(Fe). The intimate contact between the CNNSs and the MOF particles is found to promote the electron–hole separation significantly due to the formation of a heterojunction. Hence, more efficient photocatalytic dye degradation is achieved over the composites than the physical mixture.